Mitral Valve Replacement Complications : A Literature Review - Mohamad Yapanto, Alvian; Ayu Lestari, Khairani; Aidhitya, Sandhia; Widiyaningsih, Anggun; Setiani, Shella (Fakultas Ilmu Kesehatan Universitas Gresik, 2022)
Mitral valve (MV) disease are the second most common clinically significant type of valvular defect in adults. The annual incidence of degenerative MV disease in developed countries is estimated to be between 2% and 3%. MV diseases can be treated through MV replacement or repair. Despite the fact that MV replacement is sometimes the best option for treating MV diseases, it is fraught with complications. Surgical MV repair is the gold standard for treating primary degenerative MR, with approximately 95% of patients treated in designated centers, while the remaining 5% will be considered for one of three transcatheter MV repair, transcatheter MV replacement, or percutaneous transluminal valvuloplasty. Despite the fact that MV replacement is sometimes the best option for treating MV diseases, it is fraught with complications. One of the most common postoperative complication is thromboembolism. Other complications related to MV replacement are the higher risk of re-operation compared to MV repair, endocarditis, paravalvular leaks, prosthetic valve degeneration, valve embolism or migration, and left ventricular outflow tract obstruction (LVOTO). This literature review will explore the various complications related to MV replacement.